2020
DOI: 10.1002/jcla.23560
|View full text |Cite
|
Sign up to set email alerts
|

Decreased serum exosomal miR‐29a expression and its clinical significance in papillary thyroid carcinoma

Abstract: Background Aberrant levels of circulating microRNAs (miRNAs) are potential biomarkers in papillary thyroid carcinoma (PTC) diagnosis and therapy. The aim of this study was to evaluate serum exosomal miR‐29a expression as a non‐invasive biomarker for PTC diagnosis and prognosis. Methods Quantitative reverse transcription polymerase chain reaction was applied to measure serum exosomal miR‐29a expression levels in blood samples of 119 patients with PTC and 100 control subj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 27 publications
0
21
0
Order By: Relevance
“…Finally, the remaining 12 articles, including 1164 patients and 540 controls, met the inclusion criteria ( Figure 1 ). Apart from a single study [ 25 ], all articles were conducted in China [ 21 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 ]. They were published between 2016 and 2021.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Finally, the remaining 12 articles, including 1164 patients and 540 controls, met the inclusion criteria ( Figure 1 ). Apart from a single study [ 25 ], all articles were conducted in China [ 21 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 ]. They were published between 2016 and 2021.…”
Section: Resultsmentioning
confidence: 99%
“…A total of 49 exosomal miRNAs (37 up and 12 down) were significantly deregulated in the circulation of thyroid cancer patients. Pooled meta-analysis of studies showed 16 upregulated miRNAs [ 30 , 32 , 33 , 34 , 35 ] and four downregulated miRNAs [ 26 , 28 , 32 ] in the circulatory exosomes of cancer versus normal subjects. To compare cancer and nodular goiter, 21 upregulated [ 25 , 31 , 32 , 33 ] and 9 downregulated miRNAs [ 31 , 32 ] were observed.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations